Diskusi Hadis tentang Kedudukan Perempuan - D Damanhuri (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2016)
Abstract: This article discusses the hadith about the position and status of women in the family. In a variety of classical jurisprudence (fiqh) books, discussion on women tends to be discriminatory, especially in the discussion on family guidance. The position of women is more severe than men. Women as wives and caregivers in the family have to be submissive and obedient in total to meet various forms of service to her husband. This impressed little opportunity for women to earn a living justice as the position of her husband's life. Hadiths will be disclosed wider than textstual meaning by using multiple approaches and logic. This study aims to provide a more comprehensive understanding of the meaning of the text of the hadith and dismissed accusations that lead to the view that there is a lack of humane treatment of women in the household. Abstrak: Artikel ini membahas hadis tentang posisi dan kedudukan perempuan di dalam keluarga. Dalam berbagai kitab fiqh klasik, terutama bahasan tentang tuntunan keluarga, cenderung diskriminatif, karena posisi perempuan lebih berat dibandingkan dengan lelaki. Perempuan sebagai isteri dan pengasuh rumah dalam keluarga harus tunduk dan patuh secara total dalam memenuhi berbagai wujud pelayanan terhadap suaminya, yang terkesan kecil peluang baginya untuk mendapatkan hidup berkeadilan sebagaimana posisi kehidupan suaminya sendiri. Kajian hadis tentang perempuan di sini diungkap lebih luas dari pemaknaan yang tersurat dengan tinjauan meggunakan beberapa pendekatan dan logika. Kajian ini bertujuan untuk memberikan pemahaman yang lebih komprehensif dalam pemaknaan terhadap teks hadis serta menepis tudingan-tudingan yang mengarah kepada pandangan adanya perlakuan kurang manusiawi terhadap perempuan dalam rumah tangga.